2020
DOI: 10.1016/j.actamat.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of c+a dislocations in zirconium

Abstract: Plasticity in hexagonal close-packed zirconium is mainly controlled by the glide of dislocations with 1/3 1210 Burgers vectors. As these dislocations cannot accommodate deformation in the [0001] direction, twinning or glide of c + a dislocations, i.e. dislocations with 1/3 1213 Burgers vector, have to be activated. We have performed in situ straining experiments in a transmission electron microscope to study the glide of c + a dislocations in two different zirconium samples, pure zirconium and Zircaloy-4, at r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The experimental consensus is that ⟨c + a⟩ glide occurs along the pyramidal I-w plane [73][74][75][76][77][78][79] and not the pyramidal II plane. Only Long et al [78] observed a dislocation with pyramidal II glide, but this result is suspected to be due to the presence of Nb [79]. The NNP4 predicts a stable ⟨c + a⟩ screw dislocation on the pyramidal I-w plane.…”
Section: Dislocationsmentioning
confidence: 99%
“…The experimental consensus is that ⟨c + a⟩ glide occurs along the pyramidal I-w plane [73][74][75][76][77][78][79] and not the pyramidal II plane. Only Long et al [78] observed a dislocation with pyramidal II glide, but this result is suspected to be due to the presence of Nb [79]. The NNP4 predicts a stable ⟨c + a⟩ screw dislocation on the pyramidal I-w plane.…”
Section: Dislocationsmentioning
confidence: 99%
“…From experimental investigations, it is known that these loops have a ⟨a⟩ = 1/3 ⟨1 1 2 0⟩ Burgers vector and are located close to the prismatic habit planes of the hexagonal close packed (HCP) structure [4][5][6][7][8][9]. Furthermore, it is experimentally assessed that easy dislocation glide occurs on the prismatic slip systems [10][11][12][13][14][15], basal and ⟨c + a⟩ pyramidal being the main secondary slip systems [13,[15][16][17]. The change of mechanical properties after irradiation is essentially the result of the interactions between gliding dislocations and these numerous loops, which act as obstacles against dislocation glide.…”
Section: Introductionmentioning
confidence: 99%